Introduction: struggling with innovations. Social innovations and conflicts in urban development and planning - Gabriela B. Christmann (European Planning Studies, 2020)
The number of publications on social innovations has significantly increased over the past decades. Meanwhile even policy-makers build their hopes on socially innovative solutions and their `transformative power'. However, what is still needed is a better understanding of the processes and mechanisms of social innovations. This Special Issue focuses in particular on the genesis of social innovations in the context of urban development and planning. It addresses a research gap by systematically drawing the attention to the fact that innovative ideas often meet resistance or conflict and that the implementation of novel practices is hindered. The article gives a short introduction to the current state of research in the field. It explains the many-facetted concept of social innovation, defines how socially innovative urban development and planning can be understood in this context and discusses how the role of conflicts can be described. The article not least gives an overview of the contributions. The articles show that institutional friction and resistance are normal concomitants of innovation processes. This does not mean that conflicts necessarily result in the failure or delay of socially innovative developments. In cases where they are constructively processed, they rather lead to progress.
Keywords: 710; Social innovations; Urban planning; Urban development; Professional communities; Conflicts; Social process